2003
DOI: 10.1055/s-2003-40468
|View full text |Cite
|
Sign up to set email alerts
|

Androgens Shorten the Longevity of Women: Sopranos Last Longer

Abstract: Earlier we found that longevity of castrati was identical to that of intact singers. These findings were in disagreement with the prevailing concept that testosterone might shorten life and might be responsible for the shorter life expectancy of men compared to women. We have now continued our research into the life expectancy of singers, considering them as a paradigm of nature to investigate life-long effects of sex hormones, and resulting in the finding that sopranos, being more oestrogenised, live signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Historical analyses suggest that the environmental pressures of infectious disease and resource availability have caused women to live longer [39]. Some research suggests that lower mortality among women could be attributable to a low-risk, healthy lifestyle [40, 41], or to lack of male hormones such as testosterone [42]. Other factors include the unequal distribution of chronic conditions, health behaviors like smoking, and differential effects of diseases on mortality [40].…”
Section: Discussionmentioning
confidence: 99%
“…Historical analyses suggest that the environmental pressures of infectious disease and resource availability have caused women to live longer [39]. Some research suggests that lower mortality among women could be attributable to a low-risk, healthy lifestyle [40, 41], or to lack of male hormones such as testosterone [42]. Other factors include the unequal distribution of chronic conditions, health behaviors like smoking, and differential effects of diseases on mortality [40].…”
Section: Discussionmentioning
confidence: 99%
“…First, Nieschlag et al (2003) evaluated androgens and estrogens’ role on lifespan beyond age 80 years in a cohort of 292 female singers from North America and Central Europe ( Nieschlag et al, 2003 ). It was found that those with body features mirroring higher testosterone levels (i.e., deeper singing voice, taller height, and increased muscle mass) had a shorter lifespan than women with estrogen-influenced features (i.e., higher singing voice, shorter height, and decreased muscle mass; Nieschlag et al, 2003 ). However, no information on whether women were receiving any hormone therapy or had taken oral contraceptives was given ( Nieschlag et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that those with body features mirroring higher testosterone levels (i.e., deeper singing voice, taller height, and increased muscle mass) had a shorter lifespan than women with estrogen-influenced features (i.e., higher singing voice, shorter height, and decreased muscle mass; Nieschlag et al, 2003 ). However, no information on whether women were receiving any hormone therapy or had taken oral contraceptives was given ( Nieschlag et al, 2003 ). Second, Jaspers et al (2017) analyzed data from 4,076 postmenopausal women enrolled in the Rotterdam Study and showed that women with longer unopposed endogenous estrogen duration had a 4% increased hazard for all-cause mortality compared to women with shorter exposure to unopposed estrogen ( Jaspers et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“… 32 After checking steroid levels in voice musicians, Nieschlag et al, found androgens might shorten and estrogens might extend life expectancy in female singers, while in male singers, the opposite is true. 33 Differences in hormones are very present in classical musicians, 1 however, performances between genders are not remarkably different.…”
Section: Genres In Folk Music: Classic Fado and Flamencomentioning
confidence: 99%